Жилища салтово-маяцких поселений в окрестностях посёлка Эльтиген (Керченский полуостров) - Пономарёв, Л.Ю. (Степи Европы в эпоху средневековья, 2012)
К вопросам типологии и эволюции раннесредневековых жилищ Восточного Крыма впервые обратился А.В.Гадло. В основу разработанного им эволюционного ряда были положены результаты раскопок в окрестностях пос.Эльти- ген (с.Героевское) на берегу Керченского пролива. В 1963-1964 гг на поселениях Героевка-6 и Героевка-3 А.В.Гадло исследовал остатки 13 жилых комплексов, к анализу которых привлёк порядка 30 построек, открытых к тому времени на Керченском полуострове и юго-восточном Крыму The excavations of A. V.Gadlo and other researchers near Eltigen (Geroievsky) settlement located on the eastern coast of the Kerch Peninsula have revealed over 20 Saltov-Maiaki dwellings. According to their design, depth level, and layout, the dwellings can be divided into five types: type I - single-chamber semidugouts with unstrengthened sides; type II - single-chamber above-ground houses; type III - single-chamber above-ground houses with utility extensions; type IV - two-chamber above-ground five-wall houses; type V - single-chamber and two-chamber above-ground houses with rounded premises attached to them. Most dwellings are well-known and have numerous analogies at other Saltov-Maiaki sites of the Crimea and beyond it. However, so far the dwellings of type V have only been found on the Kerch Peninsula.